Resource estimation of the sulfide-rich deposits of the Yuhuang-1 hydrothermal field on the ultraslow-spreading Southwest Indian Ridge - Yu, Junyu; Tao, Chunhui; Liao, Shili; Dias, Ágata; Liang, Jin; Yang, Weifang; Zhu, Chuanwei (Ore Geology Reviews, 2021)
Seafloor massive sulfide (SMS) deposits are important deep-sea mineral resources expected to occur predominantly on slow- and ultraslow-spreading mid-ocean ridges. Resource estimates are already available for some of the largest SMS deposits on slow-spreading ridges but not on ultraslow-spreading ridges. Based on geological mapping and sampling, this study investigates the distribution and content of sulfide-rich deposits in the Yuhuang-1 hydrothermal field (YHF), located on the ultraslow-spreading Southwest Indian Ridge. The sulfide-rich deposits in the YHF are composed of two areas ∼500 m apart: the southwest sulfide area (SWS) and the northeast sulfide area (NES). We calculated the volume of sulfide-rich mounds in the YHF and arrived at a total accumulation of ∼10.6 × 106 tons, including at least ∼7.5 × 105 tons of copper and zinc and ∼18 tons of gold. Furthermore, considering the coverage of layered hydrothermal sediment mixed with sulfide-rich breccias, which may have underlying massive sulfide deposits, the maximum total mass was estimated at ∼45.1 × 106 tons. This suggests that the YHF is one of the largest SMS deposits worldwide and confirm that ultraslow-spreading ridges have the greatest potential to form large-scale SMS deposits.
Keywords: Resource estimate; Seafloor massive sulfide deposits; Southwest Indian Ridge; Yuhuang-1 hydrothermal field

Evidence for mixed contribution of mantle and lower and upper crust to the genesis of Jurassic I-type granites from Macao, SE China - Quelhas, Pedro; Mata, João; Dias, Ágata (GSA Bulletin, 2021)
Abstract Much controversy has occurred in the past few decades regarding the nature of the sources, the petrogenetic processes, and the tectonic regime(s) of the Jurassic magmatism within the Southeast China magmatic belt. This study aims to contribute to the discussion with mineral chemistry, and whole-rock element and Sr-Nd-Hf-Pb isotopic geochemical data from granitic rocks and microgranular mafic enclaves from Macao, where two discrete groups of I-type biotite granites have been identified (referred to as Macao Group I [MGI] and Macao Group II [MGII]). It is proposed that the granitic magmas were generated by partial melting of infracrustal medium- to high-K, basaltic Paleoproterozoic to Mesoproterozoic protoliths (Nd depleted mantle model age [TDM2] = 1.7–1.6 Ga and Hf TDM2 = 1.8–1.6 Ga), triggered by underplating of hot mantle-derived magmas in an extensional setting related to the foundering of a previously flat slab (paleo–Pacific plate) beneath the SE China continent. The main differences between the two groups of Macao granites are attributed to assimilation and fractional crystallization processes, during which upper-crustal Paleozoic metasediments were variably assimilated by MGI magmas. This is evidenced by an increase in initial 87Sr/86Sr ratios with degree of evolution, presence of metasedimentary enclaves, and high percentage of zircon xenocrysts with Paleozoic ages. In addition, other processes like late-stage fluid/melt interaction and magma mixing also left some imprints on granite compositions (rare earth element tetrad effect plus non–charge-and-radius-controlled behavior of trace elements and decoupling between different isotope systems, respectively). The distribution of isotopically distinct granites in SE China reflects the nature of the two Cathaysia crustal blocks juxtaposed along the Zhenghe-Dapu fault.

Geological Map of the Macao Special Administrative Region (China) - Quelhas, P; Borgens, R; Dias, Ágata; Ribeiro, L; Costa, P; Mata, J (Journal of Maps, 2021)

Geology of the Macao Special Administrative Region (China) - Quelhas, Pedro; Borges, Ricardo; Dias, Ágata Alveirinho; Ribeiro, Maria Luísa; Costa, Pedro; Mata, João (Journal of Maps, 2021)
A 1:12,000 geological map of the Macao Special Administrative Region has been produced through detailed field work supported by petrographic, mineralogical, geochronological and geochemical data obtained in previous studies. This map aims to represent a reliable tool to understand the geological evolution of the region and for management of the territory. The geology of Macao is dominated by two groups of Jurassic granitic rocks belonging to an intrusive suite located along the coast of Southeast China: Macao Group I (MGI: 164.5 ± 0.6 to 162.9 ± 0.7 Ma) and Macao Group II (MGII: 156.6 ± 0.2 to 155.5 ± 0.8 Ma), including the associated microgranite, aplite and pegmatite dikes and quartz veins. Remnants of the metasedimentary wall-rock are present as Devonian xenoliths enclosed within the granites. Younger Jurassic to Cretaceous andesite to dacite dikes (150.6 ± 0.6 to <120 Ma) intrude the granitic rocks. Additionally, Quaternary sedimentary deposits cover the older lithologies.
Keywords: Jurassic; Macao (South China); Mesozoic; geological map; granites; magmatic rocks

Magmatic Evolution of Garnet-Bearing Highly Fractionated Granitic Rocks from Macao, Southeast China: Implications for Granite-Related Mineralization Processes - Quelhas, Pedro; Mata, João; Dias, Ágata (Journal of Earth Science, 2021)
The widespread W-(Mo)-Sn-Nb-Ta polymetallic mineralization in Southeast (SE) China is genetically associated with Mesozoic highly fractionated granitic rocks. Such rocks have enigmatic mineralogical and geochemical features, making its petrogenesis an intensely debated topic. To better understand the underlying magma evolution processes, petrography, garnet chemistry and whole-rock major and trace element data are reported for Jurassic highly fractionated granitic rocks and associated microgranite and aplitepegmatite dikes from Macao and compared with coeval similar granitic rocks from nearby areas in SE China. Despite the fact that the most evolved rocks in Macao are garnet-bearing aplite-pegmatite dikes, the existence of coeval two-mica and garnet-bearing biotite and muscovite granites displaying more evolved compositions (e.g, lower Zr/Hf ratios) indicates that the differentiation sequence reached higher degrees of fractionation at a regional scale. Although crystal fractionation played an important role, late-stage fluid/melt interactions, involving F-rich fluids, imparted specific geochemical characteristics to Macao and SE China highly fractionated granitic rocks such as the non-CHARAC (CHArge-and-RAdius-Controlled) behavior of trace elements, leading, for example, to non-chondritic Zr/Hf ratios, Rare Earth Elements (REE) tetrad effects and Nb-Ta enrichment and fractionation. Such process contributed to the late-stage crystallization of accessory phases only found in these highly evolved facies. Among the latter, two populations of garnet were identified in MGI (Macao Group I) highly fractionated granitic rocks: small grossular-poor euhedral grains and large grossular-rich skeletal garnet grains with quartz inclusions. The first group was mainly formed through precipitation from highly evolved Mn-rich slightly peraluminous melts under low-pressure and relatively low temperature (∼700 °C) conditions. Assimilation of upper crust metasedimentary materials may have contributed as a source of Mn and Al to the formation of garnet. The second group has a metasomatic origin related to the interaction of magmatic fluids with previously crystallized mineral phases and, possibly, with assimilated metasedimentary enclaves or surrounding metasedimentary strata. The highly fractionated granitic rocks in Macao represent the first stage in the development of granite-related W-(Mo)-Sn-Nb-Ta mineralization associated with coeval more evolved lithotypes in SE China.